Measuring systematic risk from managerial organization capital. (23rd August 2021) - Yildirim, Alev; Allen, Linda
Abstract: Organization capital (OC) constitutes a firm's unique, hard‐to‐mimic, hard‐to‐transfer culture, internal knowledge and language, policies and procedures, growth opportunities and information technology, brand name and any other aspects that are not directly related to the production process. In order to disentangle value enhancement from agency costs inherent in the OC, we calibrate systematic risk premiums from the loss of managerial OC rents by decomposing OC into: (1) portable economic rents in the form of disclosed executive compensation and (2) a strategic component that comprised undisclosed, non‐portable OC rents mixed with agency costs. Shareholders in firms with high strategic component (not the portable component) earn an annual systematic risk premium of 4.6%. Disclosures revealing the breakdown between OC and agency costs in the strategic component (earnings surprises, managerial obfuscation and stock mispricing) as well as corporate governance eliminate this risk premium by revealing the OC rents in strategic component and increasing OC portability.